Pengaruh Brand Image, Kualitas Produk dan Promosi terhadap Minat Beli Konsumen pada Joko Café And Eatery di Kota Blitar - Risma Kumillaella; Eko Adi Susilo; Indria Guntarayana (Transgenera: Jurnal Sosial, Politik dan Humaniora, 2025)
This research aims to carry out an analysis of the influence of brand image, product quality and promotion on consumer purchasing interest at Joko cafe and Eatery Blitar. The research method used in this research is quantitative. Quantitative methods are research data in the form of numbers and analysis using statistics. Data collection techniques using questionnaires, observation and structured interviews. The population of this research is the total number of consumers from Joko Café and Eatery in Blitar, East Java, totaling 50 consumers. The results of this research, through partial brand image, have a significant effect on buying interest. This can be proven through the significance value of the product quality variable of 0.002 < 0.05. Product quality has a significant effect on purchasing interest. This can be proven through the significance value of the product quality variable of 0.004<0.05. Promotions have a significant effect on purchasing interest. This can be proven through the significance value of the product quality variable of 0.000 < 0.05.